Pengaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai di Kantor Dinas Pendidikan Daerah Provinsi Sulawesi Utara - Mamesah, Merlinda; Itje Pangkey; Abdul R. Dilapanga (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This study aims to analyze the influence of the work environment and work discipline on employee job satisfaction at the Regional Education Office of North Sulawesi Province. The research employed a quantitative approach, utilizing primary data collected through questionnaires. The findings indicate that the work environment has a significant partial effect on employee job satisfaction. Additionally, work discipline also significantly influences job satisfaction. Simultaneously, the work environment and work discipline collectively have a significant impact on employee job satisfaction at the office. These findings highlight that fostering a conducive work environment and enforcing effective work discipline can enhance employee satisfaction. This research provides valuable insights into human resource management, particularly in creating a positive workplace atmosphere and improving employee discipline levels to achieve optimal job satisfaction